How the Aspis Locked Citizen-Soldiers in and Others Out: An Essay - Paarmann, Bjørn (Classica et Mediaevalia, 2026)
This essay builds on two papers by Mogens Herman Hansen (2008; 2010), which both used mechanisms of exclusion, particularly regarding women and foreigners, to illuminate the nature of civic belonging in the polis. Expanding this approach, the essay asks why the Greeks, and especially, it seems, the Athenians, developed unusually formalised practices of inclusion and exclusion. The author’s interest arises from a comparison between modern Denmark and Switzerland, where women obtained enfranchisement fifty years apart. For the author, this gap shows that the ideal of the citizensoldier tends to exclude the political participation of other groups. Hansen himself used the Swiss Landsgemeinden as the only historical parallel to Athenian democracy, but he did not address their exclusionary nature. I will examine how solidarity and citizenship were constructed through boundary-making, analysing the symbolic, material, and institutional mechanisms by which Athenian civic identity was created and maintained.